E-Carnet Resumption and Repository System for Bus Line Commuters - Sujatha V; E.A. Mary Anitha (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
E-Carnet Resumption and Repository System for Bus Line Commuters is an ongoing venture which is very useful for the passengers. Resumption can be done using any two id proof and using credit card for paying money. This online bus pass Resumption application will help people to save their time and repository the bus passes without standing in a line for hours near counters. At first individuals need to enlist with the application by submitting points of interest of photograph, address proof, any two id verification and required subtle elements and submit through on the web. The application will verify the details and if all proves are verified then followed by transaction will be held. After that the pass will automatically generating and send it through mail. You can even repository using credit card or wire transfer methods.  This system can be used in bus transport undertaking services. Using the system in government and private sectors can exclude the use of human efforts and saves lot of money and time. This system also used to finding the route for Different places. The route information updates admin control so user trusts the valid paths. User locations are tracking using GPS tracker.